Fluid Activity Detection in The Kendalisodo Geothermal Manifestation, Semarang, Indonesia, using Microtremor Analysis of The Vp/Vs Ratio - Udi Harmoko; Sorja Koesuma; Muhammad Irham Nurwidyanto (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2026)
Experimental methods using microtremor recordings can identify site effects in moderate seismic activity areas with many ground motion records and high noise levels in urban or industrial contexts. Using observation data from several sites makes this survey easy to get consistent results. This study uses microtremors, Vp/Vs ratio, Poisson's ratio, and Vs30 analysis to identify thermal aquifer sources and recharge sites around the Kendalisodo geothermal manifestation. Vp/Vs ratios were calculated at 24 noise measurement locations. The Vp/Vs ratio and its alterations are examined.  This study also examined the distribution of VS30, the predominant single-value metric that most accurately characterises seismic soil. Poisson's ratio varies from 0.20 to 0.49, with a 0.45 anomaly associated with the geothermal spring signifying fluid-saturated regions. The Vs30 values are approximately 1300 m/s near the geothermal manifestation, indicating the presence of stiff to strongly consolidated igneous rock, as per geological evaluations. Moreover, reduced values of the Vp/Vs ratio indicate the presence of high-porosity regions that enable the movement of geothermal fluids. The study's results become clearer after looking at the Poisson ratio distribution, which shows a value of 0.45 near the manifestation. Multiplying the compressional and shear wave velocities shows an area with a lot of holes in the rock. The bedrock type, based on geological data, matches the shear wave velocity value around the manifestation, which means that hard rock, specifically igneous rock, is pushing through.